Stocks, Bonds, and Long-Run Consumption Risks - Hasseltoft, Henrik (Journal of Financial and Quantitative Analysis, 2012)
Abstract I evaluate whether the so-called long-run risk framework can jointly explain key features of both equity and bond markets as well as the interaction between asset prices and the macroeconomy. I find that shocks to expected consumption growth and time-varying macroeconomic volatility can account for the level of risk premia and its variation over time in both markets. The results suggest a common set of macroeconomic risk factors operating in equity and bond markets. I estimate the model using a simulation estimator that accounts for time aggregation of consumption growth and utilizes a rich set of moment conditions.